Socio-ecological perspectives on the carbon absorption process of tea plants (Camellia sinensis): Age-based estimates at Tambi plantation - Yusa, Farras M (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: As an effort to reduce current climate change, conservation measures such as carbon stock measurements are needed. Tea plants are a suitable commodity for transforming towards low carbon production because perennial plants such as can absorb and store more carbon than seasonal agricultural crops. Methods: Sampling was carried out using a random sampling method that was taken randomly to represent a population for each block number. Data collection for the study was carried out by taking 3 soil and plant samples at each age of the tea plant with an age of 10 years, 30 years, 40 years, and 100 years. The plant samples taken were leaves, stems, roots, and litter. The soil samples taken were soil with a depth of 0-10 cm, 10-20 cm, and 20-30 cm with disturbed and undisturbed soil sampling. Findings: The total carbon stock value of tea plants stored in the Pemandangan Block UP Tambi is 63.17 tons/ha in 10-year-old tea plants; 67.26 tons/ha in 30-year-old tea plants; 67.87 tons/ha in 40-year-old tea plants; and 69.40 tons/ha in 100-year-old tea plants. The NDVI value obtained has a range of 0.384 - 0.557 which does not really reflect the actual age of the plant because of the process of pruning tea plant shoots which is carried out every four years. This results in the spectral radiation of tea plant vegetation even though the age of the plant is very different. Conclusion: The Pemandangan Block of the Tambi Plantation Unit contains tea plants aged 10, 30, 40, and 100 years with an NDVI range of 0.384 to 0.557, where satellite-derived vegetation indices do not represent actual plant age due to replanting and pruning, making them unsuitable for soil carbon stock estimation. Novelty/Originality of this article: This study offers novelty by integrating field-based carbon stock measurements of tea plants with variations in plant age and Sentinel-2A remote sensing analysis, providing a unique contribution to understanding the relationship between soil properties, biomass, and carbon storage capacity in tea plantations, which has not been extensively explored in previous research.